ChemInform Abstract: [{Ni4(OH)3AsO4}4 (B‐α‐PW9O34)4]28‐: A New Polyoxometalate Structural Family with Catalytic Hydrogen Evolution Activity. Issue 10 (February 2016) - Lv, Hongjin; Chi, Yingnan; van Leusen, Jan; Koegerler, Paul; Chen, Zheyuan; Bacsa, John; Geletii, Yurii V.; Guo, Weiwei; Lian, Tianquan; Hill, Craig L.
Abstract: Na28 [{Ni4 (OH)3 AsO4 }4 (B‐α‐PW9 O34 )4 ] ·120H2 O is prepared by reaction of Ni(OAc)2, ≈3 equiv.